2019
DOI: 10.1080/00952990.2019.1634086
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis effects on brain structure, function, and cognition: considerations for medical uses of cannabis and its derivatives

Abstract: Background-Cannabis is the most widely used illicit substance worldwide, and legalization for recreational and medical purposes has substantially increased its availability and use in the United States. Objectives-Decades of research have suggested that recreational cannabis use confers risk for cognitive impairment across various domains, and structural and functional differences in the brain have been linked to early and heavy cannabis use. Methods-With substantial evidence for the role of the endocannabinoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 203 publications
(244 reference statements)
1
55
0
14
Order By: Relevance
“…Además, la dependencia al cannabis es responsable de una menor participación en actividades y relaciones académicas, menores ingresos, embarazos no planificados, enfermedades mentales, mayores tasas de desempleo y participación en otras conductas de riesgo (Khalsa y Baler, 2019; Oficina de las Naciones Unidas contra la Droga y el Delito, 2018). No obstante, el cannabis se ha asociado con algunos efectos beneficiosos; las afecciones más comunes por las que los médicos recomiendan el consumo de marihuana son dolor, náuseas y vómitos persistentes, mejora del sueño y ansiedad (Burggren, Shirazi, Ginder y London, 2019;Fiz, Durán, Capella, Carbonell y Farré, 2011).…”
Section: Vulnerable Populationsunclassified
“…Además, la dependencia al cannabis es responsable de una menor participación en actividades y relaciones académicas, menores ingresos, embarazos no planificados, enfermedades mentales, mayores tasas de desempleo y participación en otras conductas de riesgo (Khalsa y Baler, 2019; Oficina de las Naciones Unidas contra la Droga y el Delito, 2018). No obstante, el cannabis se ha asociado con algunos efectos beneficiosos; las afecciones más comunes por las que los médicos recomiendan el consumo de marihuana son dolor, náuseas y vómitos persistentes, mejora del sueño y ansiedad (Burggren, Shirazi, Ginder y London, 2019;Fiz, Durán, Capella, Carbonell y Farré, 2011).…”
Section: Vulnerable Populationsunclassified
“…Behaviors such as use and misuse of illicit substances often cluster empirically within the externalizing domain of psychopathology [78][79][80][81], typically with early onset, common etiology, and traits including sensation-seeking and impulsivity [82][83][84]. People who are recreational cannabis users seeking the sensation of feeling high are likely to differ from people who are medical patients [85,86] seeking marijuana for relief of pain or other symptoms and who are not typically characterized by externalizing traits [87,88]. People who are medical marijuana users may therefore differ in numerous ways from people who are recreational users in whom cognitive effects have mainly been studied to date, including later onset of use and complicating medical problems.…”
Section: People Who Are Medical Cannabis Users Vs People Who Are Recmentioning
confidence: 99%
“…Interestingly, a meta-analysis investigating whether these brain function altercations persist on fMRI with abstinence, showed that these altercations clearly persist past 25 days abstinence in adolescent users – despite no detectable THC in urine [ 18 ]. Since the endocannabinoid system plays a role in neuroplasticity [ 19 , 20 ], and neuromaturation is prevalent during adolescence [ 21 ], it is plausible that exogenous cannabinoids alters the neurodevelopmental maturation during this period – suggesting a period of vulnerability [ 8 ].…”
Section: Introductionmentioning
confidence: 99%